2018
DOI: 10.1089/fpd.2017.2362
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance ofStaphylococcus aureusIsolates from Dairy Cows and Genetic Diversity of Resistant Isolates

Abstract: Staphylococcus aureus is a frequent and major contagious mastitis bacterial pathogen. The antibiotic treatment cure rates vary considerably from 4% to 92%. Staphylococcus aureus readily becomes resistant to antibiotics, resulting in persistent noncurable intramammary infection that usually results in culling of infected animals. Because of its notorious ability to acquire resistance to the commonly used as well as last resort antimicrobials such as methicillin and vancomycin and the development of multidrug-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 52 publications
3
47
2
3
Order By: Relevance
“…A similar study in dairy cattle in Tennessee also established a variation of prevalence of antibiotic resistance of S. aureus, with an increasing trend in tetracycline resistance [ 40 ]. These conclusions followed the report identifying the predominant antibiotic groups used in animal health in South Africa from 2014 to 2015, as the growth promoters (animal use only antibiotics) (62%) followed by tetracyclines (17%) and macrolides (11%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study in dairy cattle in Tennessee also established a variation of prevalence of antibiotic resistance of S. aureus, with an increasing trend in tetracycline resistance [ 40 ]. These conclusions followed the report identifying the predominant antibiotic groups used in animal health in South Africa from 2014 to 2015, as the growth promoters (animal use only antibiotics) (62%) followed by tetracyclines (17%) and macrolides (11%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As generalised models, they allow a nonlinear relationship between the dependent variable (variable to be explained) and the model parameters [ 50 ]. In the univariate multivariable GLMM [ 40 ], the drug-specific antibiotic resistance of all S. aureus isolates was used as the dependent variable. As it is a binomial variable a logit link function was used.…”
Section: Methodsmentioning
confidence: 99%
“…The resistance of microbial isolates to a drug was also determined in terms of percent isolates showing resistance to a specific drug. Relatively the highest resistance frequency was observed towards Methicillin as compared to other antibiotics used against Gram-positive isolates [5,15]. A similar level of resistance was observed in Gram-negative bacterial isolates towards Cefixime, Cefuroxime, and Linezolid.…”
Section: Discussionmentioning
confidence: 52%
“…Different sets of rice were mixed; if these vanished then detection of B. cereus would be difficult in fried rice. The methicillin-resistant Staphylococcus aureus infections have been reported in the USA for up to 30 years [5,15]. Clostridium perfringens is usually found in raw meat, soil and the intestinal tract of humans [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A similar study in dairy cattle in Tennessee also found that there was a variation of prevalence of antimicrobial resistance of S. aureus, with an increasing trend in tetracycline resistance [1]. This was also in accordance with the report which showed that the predominant antimicrobial groups used in animal health in South Africa from 2014 to 2015, were the growth promoters (animal-use-only antimicrobials) (62%) followed by tetracyclines (17%) and macrolides (11%) [23].…”
Section: Resultsmentioning
confidence: 69%